Implementation of Customer Due Diligence Principles on Financial Service Companies in Preventing and Eradicating Criminal Action of Money Laundering in Medan - Sunarmi Sunarmi; Detania Sukarja; Tri Murti Lubis (Universitas Medan Area, 2022)
This study discusses about the implentation of customer due diligince principles on financial service companies in preventing and eradicating criminal action of money laundering in Medan. Indonesia has many favorable factors for conducting money laundering, so it does not doubt that Indonesia is labeled as a non-cooperative country combating money laundering crimes. In order to prevent and eradicate money laundering, Law No. 8 of 2010 regulates the principle of customer due diligence. The study was conducted in Medan because in Medan there are many financial services industry companies that are engaged in autotyping, real state, foreign exchange, securities companies, insurance, postal, gold, jewelery, precious metals, savings and loan cooperatives and others. Secondary the data was collected through library studies by inventorying a number of laws and regulations related to money laundering. The result shows that Principle The Customer Due Diligence has a strong legal basis in various regulations in the field of money laundering and in the Financial Services Authority regulations as in Article 18 Paragraph (2) of Law No. 8 of 2010 and Bank Indonesia Regulation (PBI) No. 3/10 / PBI / 2001 concerning Application of Know Your Customer Principles as last amended by PBI No. 5/21 / PBI / 2003. in 2009, PBI No. 5/21 / PBI / 2003 concerning Application of Know Your Customer Principles.